The Efficacy of a Validated Strategic Intervention Material in Multiplication of Fractions - Mangisel , Floriza P. (RIRAI Publisher, 2025)
This study investigated the efficacy of a Validated Strategic Intervention Material (SIM), in enhancing fifth-graders' proficiency in Multiplying Fractions. A pretest-posttest quasi-experimental design was employed with 43 learners of Hamogaway Elementary School as the participants of the study, divided into control and experimental groups. The learners in the experimental group were taught using the SIM, while the control group received traditional instruction. The results revealed significant improvement in the experimental group's multiplication skills compared to the control group. Learners exposed to SIM achieved a substantially higher mastery rate (62%) compared to the control group (23%). Analysis of gain scores further supported this finding. Learner feedback regarding the SIM was generally positive. The learners rated highly the content, clarity, applicability, usefulness, and format of the SIM. Areas for minor improvement included factual accuracy of information, promoting independent learning, and clarity in specific sections. Based on the findings, the study recommends widespread adoption of the SIM, teacher training for effective implementation, further research on learning styles and addressing challenges, and dissemination of the improved SIM for broader impact.